2020
DOI: 10.3389/fnagi.2020.593833
|View full text |Cite
|
Sign up to set email alerts
|

Contributions of Hippocampal Volume to Cognition in Healthy Older Adults

Abstract: Objective: The association between hippocampal volume and memory is continuing to be characterized in healthy older adults. Prior research suggests smaller hippocampal volume in healthy older adults is associated with poorer episodic memory and processing speed, as well as working memory, verbal learning, and executive functioning as measured by the NIH Toolbox Fluid (Fluid Cognition Composite, FCC) and Crystalized Cognition Composites (CCC). This study aimed to replicate these findings and to evaluate the ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 43 publications
2
20
0
Order By: Relevance
“…The mixed nature of these findings in developmental samples is similar to that seen in studies focused on adult samples, which have reported both a significant association between total hippocampal volume and memory (e.g., Hardcastle et al, 2020) and no association (e.g., Clark et al, 2020) or only in those with spatial expertise (i.e., London taxi drivers; Woollett & Maguire, 2011). A useful approach to gain a clearer picture of the association between the hippocampus is meta‐analysis.…”
Section: Introductionsupporting
confidence: 73%
“…The mixed nature of these findings in developmental samples is similar to that seen in studies focused on adult samples, which have reported both a significant association between total hippocampal volume and memory (e.g., Hardcastle et al, 2020) and no association (e.g., Clark et al, 2020) or only in those with spatial expertise (i.e., London taxi drivers; Woollett & Maguire, 2011). A useful approach to gain a clearer picture of the association between the hippocampus is meta‐analysis.…”
Section: Introductionsupporting
confidence: 73%
“…A study by Kim et al reported memory deficits in children with BECTS (40). Previous studies showed that verbally loaded memory tasks are strongly correlated with left hippocampal volume (41,42). Moreover, other research has shown altered static amplitude of low frequency fluctuation (sALFF) and dynamic ALFF (dALFF) in the hippocampus of BECTS patients, implying improved cognitive function (43).…”
Section: Discussionmentioning
confidence: 98%
“…A study on mild cognitive impairment and Alzheimer's disease showed a positive relationship between total hippocampus volume and MMSE score (Peng et al, 2014). Another study in Alzheimer's disease showed a positive correlation between constructional recall score and CA1 and subiculum volumes (Lim et al, 2012) and memory test outcome was also positively associated with left hippocampus volume (Hardcastle et al, 2020).…”
Section: Discussionmentioning
confidence: 99%